2016
DOI: 10.1186/s13293-016-0071-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis reveals differential regulation of the alveolar macrophage actin cytoskeleton by surfactant proteins A1 and A2: implications of sex and aging

Abstract: BackgroundSurfactant protein A (SP-A) contributes to lung immunity by regulating inflammation and responses to microorganisms invading the lung. The huge genetic variability of SP-A in humans implies that this protein is highly important in tightly regulating the lung immune response. Proteomic studies have demonstrated that there are differential responses of the macrophages to SP-A1 and SP-A2 and that there are sex differences implicated in these responses.MethodsPurified SP-A variants were used for administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 51 publications
(66 reference statements)
2
45
0
Order By: Relevance
“…In this report we showed that alveolar macrophage depletion in female mice resulted in a decrease of the eukaryotic initiation factor 2 initiation machinery, possibly resulting in decreased protein translation as well as severe alterations in mitochondria, which led to metabolic dysfunctions. A recent report raises the hypothesis of sex-dependent actin cytoskeleton regulation in alveolar macrophages (33), which has the potential to affect several processes, such as phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this report we showed that alveolar macrophage depletion in female mice resulted in a decrease of the eukaryotic initiation factor 2 initiation machinery, possibly resulting in decreased protein translation as well as severe alterations in mitochondria, which led to metabolic dysfunctions. A recent report raises the hypothesis of sex-dependent actin cytoskeleton regulation in alveolar macrophages (33), which has the potential to affect several processes, such as phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…B) As one moves from the most abundant to the less abundant CMPs the diversity of the CMP (i.e. the number of markers contributing to the particular CMP) increases (Panels A and B) shows the order [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of the top 20 CMPs from most abundant to least abundant. Then this is followed (Panels A and B) by a column giving the CMP number (5-27 CMP#; from data in Fig.…”
Section: Cmps and Pixels In Single Cellsmentioning
confidence: 99%
“…Its many functions are subject to complex regulation through autocrine [1] and paracrine mechanisms, as well as environmental factors [2], and other cell types, such as type II alveolar epithelial cells [3], which are not only responsible for the production of surfactant, a complex of proteins and lipids which is essential for lung function, but also produce a number of immunoregulatory molecules [4]. There is a large body of evidence demonstrating that the surfactant constituent, surfactant protein A (SP-A) has a profound regulatory effect on the AM, including regulating proinflammatory cytokine production, enhancing phagocytosis, and influencing actin metabolism [5][6][7]. This multi-faceted regulatory pattern may be one of the reasons for the well-documented heterogeneity of AM in the lung [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations